1990
DOI: 10.1172/jci114865
|View full text |Cite
|
Sign up to set email alerts
|

Potent toxicity of 2-chlorodeoxyadenosine toward human monocytes in vitro and in vivo. A novel approach to immunosuppressive therapy.

Abstract: Lymphoid cells were thought to be uniquely susceptible to excess 2'-deoxyadenosine (dAdo), when exposed to inhibitors of adenosine deaminase (ADA). However, we now find that human monocytes are as sensitive as lymphocytes to dAdo or to the ADA-resistant congener 2-chloro-2'-deoxyadenosine (CldAdo). Monocytes exposed in vitro to CldAdo, or to dAdo plus deoxycoformycin rapidly developed DNA strand breaks. Both the DNA damage and the toxicity of CldAdo or dAdo toward monocytes were blocked by deoxycytidine, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(61 citation statements)
references
References 50 publications
3
56
0
2
Order By: Relevance
“…dAdo has a cytotoxic effect on several human or animal immune cells [18,19]. The mouse macrophages RAW 264.7 were used to determine whether the dAdo generated by NT has the same effect.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…dAdo has a cytotoxic effect on several human or animal immune cells [18,19]. The mouse macrophages RAW 264.7 were used to determine whether the dAdo generated by NT has the same effect.…”
Section: Resultsmentioning
confidence: 99%
“…Carrera et al . showed that human monocytes were sensitive to dAdo and monocytes exposed to dAdo in vitro developed DNA strand breaks [18]. DNA damage appears to be requisite for toxicity and dAdo causes the DNA damage through effects on enzymes implicated in DNA synthesis or repair [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies have shown that 2-CdA is a highly selective anti-monocyte agent, which causes decreased monocyte function and viability and decreased IL-6 secretion [32]. Because tissue histiocytes are derived from the same stem cells as circulating monocytes, 2-CdA may thus be a rational agent for the treatment of patients with histiocytic disorders.…”
Section: Discussionmentioning
confidence: 99%